A self-reflection on providing companionship through supervision approaches of postgraduate students in geography - Ngie, Adeline (Open Science Journal, 2024)
Postgraduate education is often perceived to take place on some independent level by the student in doing most of the required work in upgrading skills and knowledge. At the same point there is need of guidance through one or more persons usually called ‘supervisor’ or ‘promoter’. During this guidance to develop knowledge and skills, relationships are established which can either challenge the people involved to grow or break down. Through the Personal Construct Theory, this paper undertakes a self-reflection within the field of Geography to understand how the various supervisory approaches can provide companionship support to students. The experiences of these approaches in higher education around other universities were also reviewed towards providing companionship for the students. The outcome shows that approach to supervision is hardly a one-size fit all scenario and certainly requires flexibility in handling the supervision process. Some approaches like the collective or collaborative or group approach certainly provide a sense of companionship in the postgraduate journey than the one-on-one approach. However, the one-on-one approach is chosen by some supervisors and students to avoid conflicts from multiple inputs, but the latter can set up a research group that still offers the sense of companionship required by students. Therefore, whatever the choice students or supervisors make, needs to consider the aspect of companionship for a holistic journey of learning.